Pengaruh Kompetensi Instruktur, Motivasi, dan Lokasi Terhadap Kepuasan Pelanggan (Studi Kasus Studio Yoga di Jakarta) - Sudarwanto, Sudarwanto; Rahman, Yoanna (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2021)
To maintain body fitness and appearance, everyone must always maintain a healthy body. Many efforts are made by humans in maintaining their body health, naniely, by doing sports at fitness center. So many yoga studios have emerged in Jakarta and its sunoundings. The purpose of the study is to analyze the effect of instructor competence, motivation and location on yoga studio customer satisfaedon and loyalty. Independent variables used are instnictor competence, motivation and location. While independent variables are satisfaction and loyalty. The research method is causality descriptive which is designed with hypothesis testing. Data is obtained by distributng questiomaires to customer (member). The sample was 74 respondents, sampling technique was accidental sampling. Data analysis method with Structural Eqiration Model (SEM) using SmartpLS version 3.2 software for student. The results showed that the instnictor's compctence had an effect on customer satisfaction. Motivation has an effect on customer satisfaction, Location has no effect on customer satisfachon. Simultaneously, Competence, Motivation and Location affect customer satisfachon